2022
DOI: 10.1155/2022/6871623
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Method for Parkinson’s Disease Diagnosis Utilizing Treatment Protocols

Abstract: It makes no difference whether a person is male or female when it comes to neurodegenerative disorders; both sexes are equally susceptible to their devastating effects. Sometimes, it is unclear why a person in their life got a condition that is well-known in the world, such as Parkinson’s disease. Other times, it is evident why the individual obtained the ailment (PD). In modern times, a variety of cutting-edge algorithms that are based on treatment protocols have been developed for the purpose of diagnosing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Destitute birth results are a critical worldwide open wellbeing issue [13,14]. Social help programs that give cash or in-kind exchanges, such as nourishment or vouchers, hold the potential to move forward birth results, but the proof on their viability has not been surveyed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Destitute birth results are a critical worldwide open wellbeing issue [13,14]. Social help programs that give cash or in-kind exchanges, such as nourishment or vouchers, hold the potential to move forward birth results, but the proof on their viability has not been surveyed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patients with a high body mass index (BMI) require intermittent mandatory ventilation (IMV) more than other patients [5]. A metaanalyses study showed that people who are older than 70 years have a higher risk for COVID-19 infection and ICU admission [6]. Other risk factors are heart failure, male gender, and chronic kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…These methodologies employ diverse sensor types, feature sets, and analysis techniques. Al-Otaibi et al highlighted in their study that, Accelerometers, force sensors, gyroscopes, and magnetometers are among the wearable sensors commonly utilised for obtaining bio-signals [6]. The study conducted by Patel et al aimed to create a wearable sensor platform that can accurately quantify the severity of tremor, bradykinesia, and dyskinesia, which are motor symptoms associated with PD.…”
Section: Brief Discussionmentioning
confidence: 99%